ESRA19-0340 Gold standard perioperative analgesia for severe chest trauma – meeting the NHS england major trauma services quality indicators. (30th August 2019) - Burtle, D; Egan, T; Pahal, G
Abstract : Background and aims: Multiple rib fractures are common in blunt chest trauma and correlate with respiratory morbidity, multisystem injury and mortality. 1 Regional anaesthesia has a major role in improving outcomes for such cases. 2 Operative rib fixation is incorporated into UK national guidelines due to consistent efficacy in massive chest wall injuries. 3 NHS England has set quality indicators for major chest wall injuries including regional analgesia within 6 hours of imaging. 4 Methods: A 37-year-old man was admitted to our hospital after a car accident. Imaging showed fractures of right posterior ribs T3-11, left first rib fracture with brachial plexopathy, haemopneumothorax and a liver laceration. He developed respiratory failure and reported severe pain despite parenteral opiates. An early thoracic epidural was inserted. We used CT images for depth guidance during placement. He underwent early fixation of five posterior ribs under general anaesthesia and was extubated immediately afterwards. Thoracic epidural remained his primary mode of analgesia for 5 days. He had 0 ventilated days, mobilised independently 1 day post injury, and was discharged to level 1 care 3 days later. Results: This patient suffered a very significant injury. We expected him to require mechanical ventilation and a prolonged critical care stay. We avoided this and its associated morbidity. Early identification and multidisciplinary input resulted in effective regional anaesthesia and rib fixation. Epidural analgesia provided perioperative analgesia sufficient to allow extubation following rib fixation and rehabilitation far earlier than expected. Conclusions: A co-ordinated rib fracture pathway prioritising timely regional anaesthesia can dramatically reduce morbidity in massive chest wall injury.